2021
DOI: 10.1017/s1092852921000869
|View full text |Cite
|
Sign up to set email alerts
|

Latency to selective serotonin reuptake inhibitor vs benzodiazepine treatment in patients with panic disorder: a naturalistic study

Abstract: Background Panic disorder (PD) is a prevalent and impairing anxiety disorder with previous reports suggesting that the longer the condition remains untreated, the greater the likelihood of nonresponse. However, patients with PD may wait for years before receiving a guideline-recommended pharmacological treatment. The widespread prescription of benzodiazepines (BDZ) for managing anxiety symptoms and disorders might delay the administration of pharmacotherapy according to guidelines (eg, selective serotonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…While benzodiazepines are associated with class-specific limitations in clinical practice, these data raise the possibility that they may have a distinct role during early treatment, perhaps while awaiting tardive response seen with SSRIs and SNRIs. Consistent with this possibility, a recent study of Italian adults with panic disorder found that the duration of untreated illness was significantly shorter for patients beginning a benzodiazepine compared to those receiving an antidepressant (64 vs. 35 months, p < 0.0001) 26 . The timing with which these treatments are introduced is also important with regard to longer-term outcomes, given that adults with a shorter period between disorder onset and beginning treatment with an SSRI predict a better response to pharmacologic treatment in patients with GAD 27 …”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…While benzodiazepines are associated with class-specific limitations in clinical practice, these data raise the possibility that they may have a distinct role during early treatment, perhaps while awaiting tardive response seen with SSRIs and SNRIs. Consistent with this possibility, a recent study of Italian adults with panic disorder found that the duration of untreated illness was significantly shorter for patients beginning a benzodiazepine compared to those receiving an antidepressant (64 vs. 35 months, p < 0.0001) 26 . The timing with which these treatments are introduced is also important with regard to longer-term outcomes, given that adults with a shorter period between disorder onset and beginning treatment with an SSRI predict a better response to pharmacologic treatment in patients with GAD 27 …”
Section: Discussionmentioning
confidence: 72%
“…Consistent with this possibility, a recent study of Italian adults with panic disorder found that the duration of untreated illness was significantly shorter for patients beginning a benzodiazepine compared to those receiving an antidepressant (64 vs. 35 months, p < 0.0001). 26 The timing with which these treatments are introduced is also important with regard to longer-term outcomes, given that adults with a shorter period between disorder onset and beginning treatment with an SSRI predict a better response to pharmacologic treatment in patients with GAD. 27 Most current treatment guidelines and recommendations focus on overall improvement [28][29][30][31] rather than on the trajectory of improvement.…”
Section: Discussionmentioning
confidence: 99%